The effects of caffeine ingestion on measures of rowing performance: A systematic review and meta-analysis - Grgic, J.; Diaz-Lara, F. J.; Del Coso, J.; Duncan, M. J.; Tallis, J.; Pickering, C.; Schoenfeld, B. J.; Mikulic, P. (Nutrients, 2020)
The purpose of this paper was to conduct a systematic review and a meta-analysis of studies examining the acute effects of caffeine ingestion on measures of rowing performance. Crossover and placebo-controlled experiments that investigated the effects of caffeine ingestion on measures of rowing performance were included. The PEDro checklist was used to assess the methodological quality of the included studies. Seven studies of good and excellent methodological quality were included. None of the included studies examined on-water rowing. The majority of studies that were included in the meta-analysis used a 2000m rowing distance with only one using 1000m distance. Results of the main meta-analysis indicated that caffeine enhances performance on a rowing ergometer compared to placebo with a mean difference of -4.1 s (95% confidence interval (CI): -6.4, -1.8 s). These values remained consistent in the analysis in which the study that used a 1000m distance was excluded (mean difference: -4.3 s; 95% CI: -6.9, -1.8 s). We also found a significant increase in mean power (mean difference: 5.7 W; 95% CI: 2.1, 9.3 W) and minute ventilation (mean difference: 3.4 L/min; 95% CI: 1.7, 5.1 L/min) following caffeine ingestion. No significant differences between caffeine and placebo were found for the rating of perceived exertion, oxygen consumption, respiratory exchange ratio, and heart rate. This meta-analysis found that acute caffeine ingestion improves 2000m rowing ergometer performance by ~4 s. Our results support the use of caffeine pre-exercise as an ergogenic aid for rowing performance. Keywords: caffeine; ergogenic aid; performance-enhancing effect